The Food Bank and Food Pantries Help Food Insecure Participants Maintain Fruit and Vegetable Intake During COVID-19 - Bertmann, Farryl; Rogomentich, Katherine; Belarmino, Emily H.; Niles, Meredith T. (Frontiers in Nutrition, 2021)
Charitable food services, including food banks and pantries, support individual and households' food access, potentially maintaining food security and diet quality during emergencies. During the COVID-19 pandemic, the use of food banks and pantries has increased in the US. Here we examine perceptions of the food bank and food pantries and its relationship to food security and fruit and vegetable (FV) intake during the first six months of the COVID-19 pandemic, using a statewide representative survey (n=600) of residents of Vermont. The utilization of food pantries was more common among food insecure households and households with children. Among food insecure respondents, those who did not use a food pantry were significantly more likely to report consuming less FV during the pandemic. Further, we find respondents who are food insecure and using a food pantry report consuming more FV since the onset of the COVID-19 pandemic. We found that respondents who were both food insecure and reported not using a food pantry were significantly more likely to report both a reduction in fruit consumption (b=-0.58; p=0.001) and a reduction in vegetable consumption (b=-0.415; p=0.012). These results indicate that these services may support food access and one important dimension of diet quality (FV intake) for at-risk populations during emergencies.